2020
DOI: 10.1136/thoraxjnl-2020-216377
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms 1.5–6 months after COVID-19 in non-hospitalised subjects: a population-based cohort study

Abstract: This study assessed symptoms and their determinants 1.5–6 months after symptom onset in non-hospitalised subjects with confirmed COVID-19 until 1 June 2020, in a geographically defined area. We invited 938 subjects; 451 (48%) responded. They reported less symptoms after 1.5–6 months than during COVID-19; median (IQR) 0 (0–2) versus 8 (6–11), respectively (p<0.001); 53% of women and 67% of men were symptom free, while 16% reported dyspnoea, 12% loss/disturbance of smell, and 10% loss/disturbance of taste. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
252
0
15

Year Published

2021
2021
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(297 citation statements)
references
References 8 publications
(10 reference statements)
30
252
0
15
Order By: Relevance
“…Our knowledge regarding SARS-CoV-2-related symptoms is evolving [ 23 ]. Another population-based study found that, in a cohort of non-hospitalized subjects contacted for reporting persistent symptoms, 65% reported a loss of smell and 69% loss of taste at diagnosis and 12% reported loss of smell and 10% loss of taste a median of 117 days from disease diagnosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge regarding SARS-CoV-2-related symptoms is evolving [ 23 ]. Another population-based study found that, in a cohort of non-hospitalized subjects contacted for reporting persistent symptoms, 65% reported a loss of smell and 69% loss of taste at diagnosis and 12% reported loss of smell and 10% loss of taste a median of 117 days from disease diagnosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…After about 5 weeks, we sent a postal reminder to non-respondents. Details of the study design have previously been reported [10].…”
Section: Survey Of Non-hospitalized Subjectsmentioning
confidence: 99%
“…1 The long-term outcome for these patients is unknown. However, recent studies indicate potential long-term complications ranging from disturbance of taste/ smell, 2 cough, 3 fatigue and dyspnoea [2][3][4][5] to more pronounced cardiac, 6 respiratory 3 4 7 and cognitive dysfunction. 3 7…”
mentioning
confidence: 99%